A Study on Effective Dose to Patients and Workers During Diagnostic X-ray Procedure in UTHM Health Centre - Shamsuddin, Zaida; Taat, Zulkifli; Mohamed Johar, Saffuwan (Journal of Science and Technology, 2018)
Effective dose is used as a reference limit to measure the total health risk from the radiation exposure to the body. Over exceeding the limit of effective dose could result in a high possibility of developing radiation-induced cancer. The aim of this research is to measure the effective dose to patients and workers during the diagnostic X-ray procedure in UTHM Health Centre. Effective dose to radiation workers is estimated by calculating the radiation dose in the controlled and supervised area. Pen dosimeter is used for dose measurement. The pen was placed at numerous spots inside the radiation facility to study the effective dose with respect to distance and shielding materials present. An ANSI patient-equivalent phantom was developed to simulate the real patient absorption and scattering during X-ray diagnostic examination for extremity, chest, skull, and lumbar. Results show that the lowest annual effective dose is measured by the door leaf which is 3.83 mSv per year while the highest is on the erect bucky stand that is 48.10 mSv per year. The annual effective dose in the supervised area and the ESE values of ANSI patient-equivalent phantoms (in mR per projection) is found to be under the reference dose limit. This finding suggested that the radiation protection principles are obeyed, with the effective dose to the radiation workers as well as patients is in the range of reference dose limit.